The COVID-19 Effect of Institutional Holdings on Firm Profitability: An Industry Analysis - Kim, Haksoon (Journal of Applied Business and Economics, 2024)
We investigate the effect of institutional holdings change on firm value change one year before and after the COVID-19 pandemic for US and global industry. Using the firm value change measures of return on equity or economic value-added changes, we find a positive relationship between institutional holdings change and firm value change one year after the COVID-19 pandemic. Specifically, the positive relationship is more pronounced for global industry. The result implies that the positive effect of institutional holdings on firm value still holds one year after the COVID-19 pandemic. It implies the global industry is more sensitive to institutional holdings.